Pengaruh Product Quality, Price, Location Dan Service Quality Terhadap Customer Satisfaction CFC (California Fried Chicken) Malang (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2019) - Achmad Hasnin Wildani; Ronny Malavia Mardani; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract In Indonesia the development of the fast food industry is increasing. Indonesia is one of the fast food enthusiasts, although not as high as in other countries. One of the benchmarks for fast food restaurants to grow rapidly is because of opportunities from consumers. One of these fast food restaurants is CFC (California Fried Chicken). The purpose of research with this type of explanatory research and quantitative approach is to find out and analyze product quality, price, location and service quality on customer satisfaction, either simultaneously or partially. Sampling using purposive sampling to determine the number of samples using the Malhotra formula and then found a total of 105 respondents. This research method uses multiple linear regression analysis with SPSS analysis tool. Based on the results of this study product quality, price, location and service quality simultaneously and partially have an influence on customer satisfaction. Keywords: Product Quality, Price, Location, Service Quality, Customer Satisfaction